The Influence of Background Information in Translation: Quantity vs. Quality or Both? - Kim, Haeyoung (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThe purpose of this article is to explore ways to provide effective as well as practical teaching tools that can be utilized in translation courses for undergraduate students. The present study specifically focuses on the effect of having access to background information of the translation. Two groups are compared for this aim. One group was asked to conduct background research on the translation topic prior to engaging in the translation while the other group only had access to dictionaries to carry out the identical task. Students were asked to complete translations from Korean into English. Outputs of the two groups were compared to assess the impact of background information. The quantity and quality of background information were also analyzed to examine their influence on the quality of translation.